2018
DOI: 10.1038/s41598-018-20858-4
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia augments alloimmune injury through IL-6-driven CD4+ alloreactivity

Abstract: Ischemia reperfusion injuries (IRI) are unavoidable in solid organ transplantation. IRI augments alloimmunity but the mechanisms involved are poorly understood. Herein, we examined the effect of IRI on antigen specific alloimmunity. We demonstrate that ischemia promotes alloimmune activation, leading to more severe histological features of rejection, and increased CD4+ and CD8+ T cell graft infiltration, with a predominantly CD8+ IFNγ+ infiltrate. This process is dependent on the presence of alloreactive CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 68 publications
1
34
1
Order By: Relevance
“…Though IL-17 levels in posttransplant MLR cultures were suppressed in Cohort C but not in Cohort B, we did not see a significant difference between the Cohorts in the frequency of IFN-γ-secreting T cells in response to irradiated donor PBLs in ELISPOT assays. Several studies have demonstrated that donor-specific alloimmune responses can be mediated through the production of cytokines other than IFN-γ including IL-6 40,41 and IL-17 4244 and that CD4 + T cells with indirect specificity can mediate skin graft rejection in the absence of IFN-γ 19,45 . These findings suggest that our ADL infusions and one DRB matching did play important roles in tolerance induction and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Though IL-17 levels in posttransplant MLR cultures were suppressed in Cohort C but not in Cohort B, we did not see a significant difference between the Cohorts in the frequency of IFN-γ-secreting T cells in response to irradiated donor PBLs in ELISPOT assays. Several studies have demonstrated that donor-specific alloimmune responses can be mediated through the production of cytokines other than IFN-γ including IL-6 40,41 and IL-17 4244 and that CD4 + T cells with indirect specificity can mediate skin graft rejection in the absence of IFN-γ 19,45 . These findings suggest that our ADL infusions and one DRB matching did play important roles in tolerance induction and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence highlights the importance of novel strategies that can reduce intra-graft inflammatory responses effectively 13,14 . Intra-graft inflammatory responses have increasingly received attention as an instigator of the alloimmune response 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that ischemia promotes alloimmune activation, leading to more severe histological features of rejection and increased leukocyte graft infiltration. 41 Despite the effectiveness of the single graft pre-treatment with AP-1 dODN in our study, the restricted dODN stability is a further limiting factor. As it is possible to generate intracellularly any single-stranded DNA, 42 a dODN expression system generating therapeutic nucleic acids in bioactive form may provide an improved therapeutic approach for continuous generation of the dODN in cells of the graft vessel wall, which may have an even more pronounced effect on neointima formation.…”
Section: Discussionmentioning
confidence: 72%